Highly efficient recyclable hydrated-clay supported catalytic system for atom transfer radical polymerization - Munirasu, Selvaraj; Aggarwal, Ravi; Baskaran, Durairaj (Chemical Communications, 2009)
Atom transfer radical polymerization of methacrylates has been performed using hydrated natural clay as a support for a CuBr(2)-ligand complex and the supported clay catalyst has been recycled for 21 batch polymerizations without losing its activity.